Pelatihan Learning Management System (LMS) bagi Para Guru Sekolah Menengah Pertama di Kabupaten Manggarai Timur - Fransiskus Jemadi; Ely Heldydiana Selamat; Yustus Sentus Halum; Imelda Wawuk; Siprianus Hame (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
There is no greater power to encourage teachers to integrate Information and Communication Technology (ICT) in the learning process until the Covid-19 pandemic occurs. The Covid-19 pandemic has changed the learning process in schools in the outermost, remote, and disadvantaged (3T) areas such as East Manggarai Regency, East Nusa Tenggara (NTT). The implementation of Distance Learning (PJJ) has just begun to be introduced to teachers to ensure that students receive appropriate educational services. Unfortunately, this PJJ did not run well or optimally. This is because the teachers do not have the experience and knowledge of Learning Management Systems (LMS) available for free such as Canvas. Therefore, the Community Service (PkM) team conducted strengthening training to increase knowledge and use of ICT for teachers at the State Junior High School (SMPN) 5 Borong, East Manggarai Regency. This activity uses presentation, demonstration (practice), and evaluation methods. This PkM activity shows that all of the participating teachers think that Canvas-based LMS training activities are beneficial and are committed to using Canvas LMS in their learning activities at school with students.